XXIV International Conference of the Chilean Computer Science Society
DOI: 10.1109/qest.2004.21
|View full text |Cite
|
Sign up to set email alerts
|

StoryMapper: A Multimedia Tool to Externalize Knowledge

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Concept maps (Acosta et al, 2004) are used to capture tacit knowledge in the form of group storytelling activity, wherein subject matter experts (SMEs) share their experiences via storytelling to create a concept map that provides a semantic and visual representation of the whole story. Sigala and Chalkiti (2007) used questionnaires and telephonic interviews as methods to elicit tacit knowledge from hotel staff in order to improve the business processes in the hotel industry.…”
Section: Methods Of Externalization (How)mentioning
confidence: 99%
See 2 more Smart Citations
“…Concept maps (Acosta et al, 2004) are used to capture tacit knowledge in the form of group storytelling activity, wherein subject matter experts (SMEs) share their experiences via storytelling to create a concept map that provides a semantic and visual representation of the whole story. Sigala and Chalkiti (2007) used questionnaires and telephonic interviews as methods to elicit tacit knowledge from hotel staff in order to improve the business processes in the hotel industry.…”
Section: Methods Of Externalization (How)mentioning
confidence: 99%
“…Experience sharing is the most common scenario for externalization, which involves sharing experiences in the form of best practices (Friedrich & van der Poll, 2007), stories (Acosta et al, 2004), and project knowledge (Chandra et al, 2015). It is observed that certain scenarios, such as strategic thinking and problem solving, mandate the participation from multiple experts, whereas other scenarios, such as decisiveness and enterprise blogging, need only a single expert for the externalization process.…”
Section: Motivational Factors (Why) and Scenarios (When) For Externalmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, stories that are told within a community of practice convey capabilities amongst the members of a group that share a common interest, even if facts, methods, solutions and ideas are not made explicit beside the story itself. Listening to stories told by experienced members in a community of practice may foster knowledge, skills, attitudes and competencies, even if facts, methods, solutions and reasons are not made explicit (Acosta et al 2004), e.g., present a multimedia tool which addresses the externalization of implicit knowledge while (Linde 2001) puts an emphasis on social knowledge that is communicated through stories, i.e. on knowledge concerning group identity and performance.…”
Section: Applications Of Storytelling In Knowledge Managementmentioning
confidence: 99%
“…StoryMapper (Acosta et al 2004) supports groups in telling a story and structures the collaboration process by assigning different roles to the members of the group. A story is modeled as conceptual map.…”
Section: R8mentioning
confidence: 99%